Religious Enculturation in Islamic Education - Nursobah, Asep; Suhartini, Andewi (International Journal of Engineering and Technology, 2018)
In Islamic education, enculturation implemented through the actualization of the behavior of learners in everyday life in school community. Enculturation values of islamic education is an attempt to embody of the values of the Islamic religion in the everyday behavior of learners, especially in schools. The research methode was descriptive, located in Purwakarta district West Java Province, Indonesia, with a sample of 6 the State Secondary School (SMPN), conducted in 2016. The data collection was done by using a questionnaire enclosed and semi-enclosed and equipped with observation and interviews. Data analyzed with quantitative and qualitative approach to describe and explore with categorization and interpretation. The research found that enculturation process of Islamic values in schools conducted through three important activities. Those are: (a) stages of values socialization; (b) habituation of behavior in accordance with the values; (c) enforcement of the rules for the establishment of appropriate behavior with values. Enculturation of Islamic values in schools through socialization, habituation to behave as well as enforcement of school discipline is proven to control the behavior of students in Islamic education. The enculturized values  as a religious value (feel oneself being watched by God), affection to peers, respectful to teachers, pious conducted through habituation, such as reading the Quran, read the Divine Name, pray before and after learning, familiarize greeting and other religious activities in school environment is proven to strengthen Islamic religion learning process for students. Those enculturation of religious values was able to control everyday behavior of students in the school. The focus of this research is the habituation of good behavior in Islamic religion education through the enculturation of religious culture in the state secondary school. This research contributes to the development of the growth of good behavior through the enculturation  values of the Islamic religion in the school.